Comparative Analysis of Presentation of Set Material in Indonesian and Fijian Mathematics Textbooks - Jesika Dwi Putriani; Ely Susanti; Cecil Hiltri Martin (Journal of Instructional Mathematics, 2025)
Textbooks are essential learning tools that significantly influence students' comprehension of mathematical concepts, including the foundational topic of sets. This study aimed to analyze how set materials are presented in Indonesian and Fijian mathematics textbooks, focusing on facts, concepts, principles and errors, cognitive levels, problem-solving, and alignment with the Programme for International Student Assessment (PISA) framework. Using a qualitative descriptive-comparative method, the study examined three textbooks: Indonesia’s KTSP (2011), Merdeka Curriculum (2022), and a Fijian mathematics book. Data were collected through document analysis. The findings revealed distinct presentation approaches: KTSP emphasizes symbols and formal definitions; the Merdeka Curriculum uses real-life contexts; and the Fijian book adopts a simple, visual style. Regarding cognitive levels, KTSP questions are mostly C1–C2, Merdeka Curriculum texkbook includes C4–C5, while Fiji remains at C1–C3. However, all three lack sufficient alignment with PISA question types. In terms of problem-solving, KTSP tends to be procedural, the Merdeka Curriculum is more reflective, and Fiji lacks problem-solving tasks. These findings highlight the need for textbooks to include more contextual and higher-order thinking problems to support students’ mathematical literacy and deeper understanding.